Positive electrode material, secondary battery, and electric device

By using the cathode materials of lithium nickel cobalt manganese oxide and lithium manganese iron oxide in secondary batteries, the problem of insufficient rate performance and circulation performance of the existing battery is solved, and better fast charging and circulation performance is achieved.

CN119400853APending Publication Date: 2025-02-07SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638619.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The rate performance and cycle performance of existing secondary batteries are insufficient, especially in long battery life and fast charging scenarios.

Method used

Using a positive electrode material containing lithium nickel cobalt manganese oxide and iron manganese lithium oxide, the structural stability and electrochemical properties of the material are improved by adjusting the lattice expansion change rate of the material and the composition of the coating layer.

Benefits of technology

It effectively improves the fast charging performance, cycle performance and safety performance of the secondary battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140310760000041
    Figure BDA0005140310760000041
  • Figure BDA0005140310760000042
    Figure BDA0005140310760000042
  • Figure BDA0005140310760000131
    Figure BDA0005140310760000131
Patent Text Reader

Abstract

The invention provides a positive electrode material, a secondary battery and electric equipment. By utilizing the characteristics of high specific capacity, high conductivity and the like of the lithium-nickel-cobalt-manganese oxide and the advantages of high structural stability, relatively good cycling stability, safety and the like of the manganese-iron-lithium oxide, the two materials are mixed to serve as the positive electrode active material; when the mixed positive electrode active material is charged from a 10% lithium removal state to a 80% lithium removal state at a rate of 0.1 C, the maximum expansion change rate delta cNCM of the crystal lattice of the lithium nickel cobalt manganese oxide in the c-axis direction is less than or equal to 2.5%, and the maximum expansion change rate delta cLMFP of the crystal lattice of the manganese iron lithium oxide in the c-axis direction is less than or equal to 2.0%; therefore, the fast charging performance, the cycle performance and the safety performance of the secondary battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of positive electrode technology, in particular to a positive electrode material, a secondary battery and an electrical device. Background Art

[0002] As an important component of secondary batteries, cathode materials play a vital role in battery performance. Ternary materials are widely used in high-end electric vehicles due to their high energy density, but safety and cost issues are the main factors restricting their widespread application.

[0003] Compared with ternary materials, lithium manganese iron phosphate materials have obvious advantages in safety and cost, but lithium manganese iron phosphate also has its own limitations, such as manganese dissolution, dual voltage platform and low conductivity, which are mainly manifested in low energy density and poor rate performance. Its application in scenarios with special requirements such as long battery life and fast charging is seriously affected. Summary of the invention

[0004] The purpose of the present application is to provide a positive electrode material, a secondary battery and an electrical device to improve the rate performance and cycle performance of existing secondary batteries.

[0005] To achieve the above-mentioned object, in a first aspect of the present application, a positive electrode material is provided, wherein the positive electrode material comprises lithium nickel cobalt manganese oxide and lithium manganese iron oxide;

[0006] When the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum expansion change rate Δc of the lattice of the lithium nickel cobalt manganese oxide in the c-axis direction is NCM ≤2.5%, the maximum expansion change rate Δc of the lattice of the manganese iron lithium oxide in the c-axis direction LMFP ≤2.0%.

[0007] As an embodiment of the present application, the molecular formula of the lithium nickel cobalt manganese oxide is Li x Ni y Co z Mn k M p O2, wherein 0.9≤x≤1.1, 0.5<y<1, 0<z<0.2, 0<k<0.5, 0≤p≤0.1, and M comprises at least one of B, Y, Nb, In, La, Zr, Ce, W, Al, Ti, Sr, Mg, Sb, V, Zn, Cu, Cr, and Fe.

[0008] As an embodiment of the present application, at least part of the surface of the lithium nickel cobalt manganese oxide also has a coating layer, and the coating layer contains oxides of one or more elements of Li, Na, B, Ca, Zn, Zr, Al, Sr, Mg, W, Y, Nb, Ti, Ru, and Mo.

[0009] As an embodiment of the present application, the manganese iron lithium oxide contains Me element, and the Me element contains at least one of Al, Ti, V, Mg, Mo, Zr, W, Sr, Cr, La, and Ce.

[0010] As an embodiment of the present application, the manganese iron lithium oxide includes primary particles having an average particle size of 50 to 200 nm.

[0011] As an embodiment of the present application, the mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron oxide in the positive electrode material is 2:8 to 8:2.

[0012] As an embodiment of the present application, when the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum deviation angle δ of the (003) crystal plane XRD diffraction peak of the lithium nickel cobalt manganese oxide is NCM (003)≤0.6°, the maximum deviation angle δ of the (011) crystal plane XRD diffraction peak of the manganese iron lithium oxide LMFP (011)≤0.3°.

[0013] In a second aspect of the present application, a secondary battery is provided, wherein the secondary battery comprises a positive electrode plate, and the positive electrode plate comprises the positive electrode material described in the first aspect of the present application.

[0014] As an implementation scheme of the present application, the mass concentration deviations of nickel and iron in the positive electrode plate are both less than 20%.

[0015] As an implementation scheme of the present application, the film resistance of the positive electrode plate is less than 1Ω.

[0016] As an embodiment of the present application, the specific surface area of ​​the positive electrode sheet is 2 to 10 m 2 / g.

[0017] As an implementation scheme of the present application, the porosity of the positive electrode plate is 10% to 40%.

[0018] According to a third aspect of the present application, an electrical device is provided, wherein the electrical device comprises the secondary battery according to the second aspect of the present application.

[0019] Compared with the prior art, the beneficial effects of this application are:

[0020] The present invention utilizes the high specific capacity and high conductivity of lithium nickel cobalt manganese oxide and the high structural stability, good cycle stability and safety of lithium manganese iron oxide, and mixes the two materials as positive electrode active materials, so that when the mixed positive electrode active materials are charged from 10% de-lithiation state to 80% de-lithiation state at a rate of 0.1C, the maximum expansion change rate Δc of the lattice of lithium nickel cobalt manganese oxide in the c-axis direction is NCM ≤2.5%, the maximum expansion change rate Δc of the lattice of manganese iron lithium oxide in the c-axis direction LMFP ≤2.0%, effectively improving the fast charging performance, cycle performance and safety performance of the secondary battery. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0022] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0023] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0024] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0025] An embodiment of the present application provides a positive electrode material, the positive electrode material comprising lithium nickel cobalt manganese oxide and lithium manganese iron oxide;

[0026] When the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum expansion change rate Δc of the lattice of the lithium nickel cobalt manganese oxide in the c-axis direction is NCM ≤2.5%, the maximum expansion change rate Δc of the lattice of the manganese iron lithium oxide in the c-axis direction LMFP≤2.0%, the "10% delithiation state" refers to the state where the ratio of the material's charged gram capacity to the theoretical gram capacity is 10%, and similarly, the "80% delithiation state" refers to the state where the ratio of the material's charged gram capacity to the theoretical gram capacity is 80%.

[0027] In some embodiments, when the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum expansion change rate Δc of the lattice of the lithium nickel cobalt manganese oxide in the c-axis direction is NCM ≤2.5%. For example, the maximum expansion change rate Δc of the crystal lattice of lithium nickel cobalt manganese oxide in the c-axis direction NCM It can be any value among 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.5%, or a range between any two values.

[0028] The maximum expansion rate of the crystal lattice of lithium nickel cobalt manganese oxide in the c-axis direction Δc NCM The specific method of obtaining is: placing a half-cell containing the positive electrode material in an in-situ XRD test mold and charging it to 4.4V at 0.1C. After starting the battery, the XRD is continuously scanned at a scanning speed of 5° / min to obtain the XRD of the positive electrode material in different delithiation states. Afterwards, the positive electrode material is subjected to XRD analysis, and the interplanar spacings d

[003] and d

[101] of the

[003] and

[101] crystal planes are obtained according to the X-ray diffraction pattern (reference standard PDF#09-0063).

[0029] The unit cell parameters a and c are calculated based on the

[003] peak and the

[101] peak, where the calculation formula is as follows:

[0030] Bragg equation: 2dsinθ=λ

[0031] Hexagonal crystal formula:

[0032]

[0033] In some embodiments, when the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum expansion change rate Δc of the lattice of the manganese iron lithium oxide in the c-axis direction is LMFP ≤2.0%. For example, the maximum expansion change rate Δc of the crystal lattice of manganese iron lithium oxide in the c-axis direction LMFP It can be any value among 0.5%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, or a range between any two values.

[0034] The maximum expansion rate of the crystal lattice of manganese iron lithium oxide in the c-axis direction Δc LMFPThe specific acquisition method is: place a half-cell containing the positive electrode material in an in-situ XRD test mold and charge it to 4.4V at 0.1C. After starting the battery, the XRD is continuously scanned at a scanning speed of 5° / min to obtain the XRD of the positive electrode material in different delithiation states. Afterwards, the positive electrode material is subjected to XRD analysis, and the interplanar spacings d

[020] , d

[011] , and d

[111] of the

[020] ,

[011] , and

[111] crystal planes are obtained according to the X-ray diffraction pattern (reference standard PDF#42-0580). The unit cell parameters b, c, and a are calculated based on the

[110] ,

[101] , and

[111] peaks, where the calculation formula is as follows:

[0035] Bragg equation: 2dsinθ=λ

[0036] Orthorhombic crystal system formula:

[0037]

[0038] In some embodiments, the lithium nickel cobalt manganese oxide has a molecular formula of Li x Ni y Co z Mn k M p O2, wherein 0.9≤x≤1.1, 0.5<y<1, 0<z<0.2, 0<k<0.5, 0≤p≤0.1, and M comprises at least one of B, Y, Nb, In, La, Zr, Ce, W, Al, Ti, Sr, Mg, Sb, V, Zn, Cu, Cr, and Fe.

[0039] In some embodiments, the M comprises at least one of Zr, W, and Sr.

[0040] In some embodiments, at least a portion of the surface of the lithium nickel cobalt manganese oxide also has a coating layer, and the coating layer contains oxides of one or more elements of Li, Na, B, Ca, Zn, Zr, Al, Sr, Mg, W, Y, Nb, Ti, Ru, and Mo.

[0041] In some embodiments, at least a portion of the surface of the lithium nickel cobalt manganese oxide further has a coating layer, and the coating layer contains an oxide of the Al element.

[0042] In some embodiments, the Dv50 of the lithium nickel cobalt manganese oxide is 3.0-10.7 μm. For example, the Dv50 of the lithium nickel cobalt manganese oxide can be any one of 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.7 μm, or a range between any two values.

[0043] In some embodiments, the manganese iron lithium oxide contains Me element, and the Me element contains at least one of Al, Ti, V, Mg, Mo, Zr, W, Sr, Cr, La, and Ce.

[0044] In some embodiments, the manganese iron lithium oxide includes a Me element, and the Me element includes Mg and / or Ti.

[0045] In some embodiments, the manganese iron lithium oxide comprises primary particles with an average particle size of 50 to 200 nm. For example, the average particle size of the manganese iron lithium oxide primary particles can be any one of 50 nm, 70 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, and 200 nm, or a range between any two values.

[0046] In some embodiments, the mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron oxide in the positive electrode material is 2:8 to 8:2. For example, the mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron oxide in the positive electrode material can be any one of 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or a range between any two values. The mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron oxide in the positive electrode material is within the above range, which can further balance the cycle performance, rate performance, safety performance and energy density of the secondary battery.

[0047] In some embodiments, when the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum deviation angle δ of the (003) crystal plane XRD diffraction peak of the lithium nickel cobalt manganese oxide is NCM (003)≤0.6°. For example, the maximum deviation angle of the (003) crystal plane XRD diffraction peak of lithium nickel cobalt manganese oxide is δ NCM (003) can be any value among 0.2°, 0.3°, 0.4°, 0.5°, 0.6°, or a range between any two values.

[0048] δ NCM The specific method of obtaining (003) is as follows: a half-cell containing the positive electrode material is placed in an in-situ XRD test mold and charged to 4.4V at 0.1C. After starting the battery, the XRD is continuously scanned at a scanning speed of 5° / min, and the XRD of the positive electrode material in different delithiation states can be obtained. Afterwards, the positive electrode material is subjected to XRD analysis, and the crystal plane angles 2θ(003) and 2θ(101) corresponding to the strongest diffraction peaks of the

[003] and

[101] crystal planes are obtained according to the X-ray diffraction spectrum (reference standard PDF#09-0063), and then the maximum deviation angles of the diffraction peaks of the

[003] and

[101] crystal planes of lithium nickel cobalt manganese oxide in the positive electrode materials in different delithiation states can be obtained.

[0049] In some embodiments, when the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum deviation angle δ of the (011) crystal plane XRD diffraction peak of the manganese iron lithium oxide is LMFP (011)≤0.3°. For example, the maximum deviation angle of the XRD diffraction peak of the (011) crystal plane of manganese iron lithium oxide is δ LMFP (011) can be any value among 0.1°, 0.2°, 0.3°, or a range between any two values.

[0050] δ LMFP The specific method of obtaining (011) is as follows: a half-cell containing the positive electrode material is placed in an in-situ XRD test mold and charged to 4.4V at 0.1C. After starting the battery, the XRD is continuously scanned at a scanning speed of 5° / min, and the XRD of the positive electrode material in different delithiation states can be obtained. Afterwards, the positive electrode material is subjected to XRD analysis, and the crystal plane angles 2θ(020), 2θ(011) and 2θ(111) corresponding to the strongest diffraction peaks of the

[020] ,

[011] and

[111] crystal planes are obtained according to the X-ray diffraction spectrum (reference standard PDF#42-0580), and then the maximum deviation angles of the diffraction peaks of the

[020] ,

[011] and

[111] crystal planes of manganese iron lithium oxide in the positive electrode materials in different delithiation states can be obtained.

[0051] In some embodiments, the molar ratio of manganese to iron in the manganese iron lithium oxide is Mn / Fe≥1. For example, the molar ratio of manganese to iron in the manganese iron lithium oxide can be any one of 5:5, 6:4, 7:3, 8:2 or a range between any two values.

[0052] In some embodiments, the Dv50 of the manganese iron lithium oxide is 0.5-1.0 μm. For example, the Dv50 of the manganese iron lithium oxide can be any value among 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, or a range between any two values.

[0053] In some embodiments, the mass percentage of carbon in the manganese iron lithium oxide is 1.5% to 2.0%. For example, the mass percentage of carbon in the manganese iron lithium oxide can be any one of 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or a range between any two values.

[0054] In a second aspect of the present application, a secondary battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode material layer arranged on at least one surface of the positive electrode collector, wherein the positive electrode material layer comprises the positive electrode material described in the first aspect of the present application.

[0055] In some embodiments, the mass concentration deviation of the nickel and iron elements in the positive electrode sheet is less than 20%. For example, the mass concentration deviation of the nickel and iron elements in the positive electrode sheet can be any one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or a range between any two values.

[0056] The density of lithium nickel cobalt manganese oxide and lithium manganese iron oxide is quite different, and segregation is easy to occur during the mixing process. When the mass concentration deviation of nickel and iron in the positive electrode plate meets the above conditions, it indicates that lithium nickel cobalt manganese oxide and lithium manganese iron oxide are mixed more evenly, and the cycle performance and rate performance of the secondary battery using the positive electrode plate can be further improved.

[0057] In some embodiments, the mass concentration deviation of nickel and iron elements in the positive electrode plate is tested by the following method: the mass concentration of the element in any 5um x5um area in the positive electrode plate can be tested by EDS element analysis combined with SEM area scanning to obtain the mass concentration of the element in the area at that position as a percentage of all elements.

[0058] In some embodiments, the diaphragm resistance of the positive electrode sheet is less than 1Ω. For example, the diaphragm resistance of the positive electrode sheet can be any one of 0.1Ω, 0.2Ω, 0.3Ω, 0.4Ω, 0.5Ω, 0.6Ω, 0.7Ω, 0.8Ω, 0.9Ω or a range between any two values. When the diaphragm resistance of the positive electrode sheet is within the above range, it can ensure that the battery has a lower internal resistance and improve the dynamic performance of the battery. The diaphragm resistance of the positive electrode sheet is tested by the ACCFilm diaphragm resistance tester.

[0059] In some embodiments, the specific surface area of ​​the positive electrode sheet is 2 to 10 m 2 / g. For example, the specific surface area of ​​the positive electrode sheet can be 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 When the specific surface area of ​​the positive electrode sheet is within the above range, it can ensure that the positive electrode sheet has a good electrolyte infiltration effect and will not produce serious side reactions.

[0060] The specific surface area of ​​the positive electrode can be tested by low-temperature nitrogen adsorption method. For details, refer to GB / T19587-2017 Gas adsorption BET method for determination of specific surface area of ​​solid substances. Sample pretreatment and degassing conditions: 220℃ / 2hrs (vacuum degassing) Sample volume: 2 / 3 of the volume of the bubble Determination method of adsorbed gas volume: static capacity method, multi-point measurement P / P0 0.060, 0.080, 0.120, 0.160, 0.20 Adsorbate: N2, 99.999% Equilibrium time: 10s Volume: Measurement mode (measured with N2) Liquid nitrogen temperature: -196℃.

[0061] In some embodiments, the electrode porosity of the positive electrode plate is 10% to 40%. For example, the electrode porosity of the positive electrode plate can be any one of 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, or a range between any two values. The porosity of the positive electrode plate can be tested by mercury intrusion, for details, refer to GB / T 21650.1-2008 for determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method.

[0062] In some embodiments, the thermal enthalpy of the positive electrode plate at 100% SOC of the secondary battery is less than 935 J / g. In some embodiments, the thermal enthalpy of the positive electrode plate at 100% SOC of the secondary battery is 418 to 933 J / g. The thermal enthalpy value is obtained by DSC testing and is obtained by calculating the peak area of ​​the DSC curve. The thermal enthalpy value is within the above range, indicating that the secondary battery has high thermal stability.

[0063] In some embodiments, the secondary battery further comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode material.

[0064] The type of negative electrode material is not specifically limited and can be selected according to actual needs. For example, the negative electrode material can be artificial graphite, natural graphite, silicon-carbon composite material, silicon oxide, hard carbon, lithium metal and lithium titanate.

[0065] The negative electrode sheet is a single-sided sheet or a double-sided sheet. When the negative electrode sheet is a single-sided sheet, the negative electrode active material layer is arranged on one surface of the negative electrode current collector. When the negative electrode sheet is a double-sided sheet, the negative electrode active material layer is arranged on both surfaces of the negative electrode current collector. The negative electrode sheet may also have a single-sided negative electrode sheet area and a double-sided negative electrode sheet area at the same time. When the negative electrode sheet has a single-sided negative electrode sheet area and a double-sided negative electrode sheet area at the same time, the thickness of the negative electrode sheet is the thickness of the double-sided negative electrode sheet area.

[0066] The type of negative electrode current collector is not particularly limited and can be selected according to actual needs. Preferably, copper foil or carbon-coated copper foil can be used.

[0067] In some embodiments, the secondary battery further comprises a separator. The type of separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, a polyethylene film, a polyvinylidene fluoride, a spandex film, an aramid film, or a multilayer composite film modified by a coating.

[0068] In some embodiments, the preparation of a secondary battery includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then winding them into a square bare cell, loading them into a battery casing, and then baking them at 65 to 95°C to remove water, injecting electrolyte, sealing, and obtaining a secondary battery after standing, hot and cold pressing, formation, clamping, capacity division and other processes.

[0069] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as one or more of polypropylene, polybutylene terephthalate, polybutylene succinate, etc.

[0070] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.

[0071] The third aspect of the present application provides an electric device, which includes the secondary battery described in the second aspect of the present application. The electric device can be an application device such as a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. The vehicle can be a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, etc.; the spacecraft includes an airplane, a rocket, a space shuttle, and a spacecraft, etc.; the electric toy includes a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc.; the electric tool includes a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and a railway electric tool, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned devices.

[0072] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.

[0073] Example 1

[0074] Embodiment 1 provides a secondary battery, and the specific preparation process of the secondary battery includes:

[0075] (1) Preparation of positive electrode materials

[0076] a) Preparation of lithium nickel cobalt manganese oxide

[0077] Step S01: Add nickel sulfate, cobalt sulfate and manganese sulfate to deionized water to prepare a nickel-cobalt-manganese sulfate solution, wherein the molar ratio of nickel, cobalt and manganese elements in the nickel-cobalt-manganese sulfate solution is Ni:Co:Mn=60:10:30. Add 2 mol / L ammonia solution and 8 mol / L sodium hydroxide solution to the solution at a uniform speed and in parallel, wherein the ammonia solution contains 0.6% tetraethylammonium hydroxide by mass, and the pH is controlled between 11.2 and 11.8 by sodium hydroxide. Nitrogen protection is used during the reaction, the stirring speed is 500 rpm, the reaction temperature is about 50°C, and the reaction time is controlled to be 24 hours to obtain a ternary precursor Ni 0.6 Co 0.1 Mn 0.3 (OH)2.

[0078] Step S02: Add the ternary precursor, lithium carbonate, zirconium oxide ZrO2, and tungsten oxide WO3 into a mixer according to the ratio of related elements in the molecular formula, wherein the ratio of the molar amount of zirconium in zirconium oxide, the molar amount of tungsten in tungsten oxide to the total molar amount of nickel, cobalt and manganese elements in the ternary precursor is 0.001:0.002:0.997; the mixed materials are put into a tubular furnace, and the temperature is raised to 900°C at 5°C / min in an oxygen atmosphere for calcination for 12 hours, and then cooled to room temperature with the furnace, and the precursor of active material particles with an average particle size Dv50 of 3.8μm is obtained by air flow crushing and classification.

[0079] Step S03: The precursor of the active material particles is coated with alumina Al2O3 and then returned to the furnace for secondary calcination, wherein the molar ratio of the precursor of the active material particles to the aluminum in the alumina is 0.997:0.003, the calcination temperature is 450°C, and the positive electrode active material NCM613 is obtained after screening.

[0080] b) Preparation of lithium iron manganese oxide

[0081] Step S01: lithium carbonate, manganese tetraoxide, ferric phosphate, magnesium sulfate, and lithium dihydrogen phosphate are weighed and prepared according to the molar ratio of Li, Mn, Fe, Mg, and P of 1:0.58:0.4:0.02:1, and added into solvent water, and the solid content is controlled at 60wt% to obtain a primary material system, and the material is ground by a ball mill for 8h to obtain a primary material system with a Dv50 of 0.2μm;

[0082] Step S02: The material obtained in step S01 is fed into a centrifugal atomizing dryer (inlet temperature of 220°C, outlet temperature of 80-100°C, atomizing gas flow rate of 50L / min, rotation speed of 1200rpm) with a solid content of 60% and subjected to spray drying to obtain a Dv50 of 50μm and a bulk density of 0.4g / cm 3 , a dry powder material having a water content of less than 3% by weight, heating the dry powder material to 400° C. at a heating rate of 2° C. / min, and keeping the temperature for 12 hours to obtain a precursor;

[0083] Step S03: 1 mol of the precursor obtained in step S02 is added to a grinding jar, followed by addition of sucrose (1.8 wt% of the precursor), MgSO4 (0.01 mol) and water, with the solid content controlled at 70 wt% to obtain a secondary material system, which is ground in a ball mill (rotation speed of 100 Hz) for 6 h to obtain a secondary material system with a Dv50 of 0.2 μm;

[0084] Step S04: The material obtained in step S03 is fed into a centrifugal atomizing dryer (inlet temperature of 280°C, outlet temperature of 80-100°C, atomizing gas flow rate of 30L / min, rotation speed of 1600rpm) with a solid content of 70wt% and subjected to spray drying to obtain a product with a Dv50 of 30μm and a bulk density of 0.2g / cm 3 , a dry powder material with a moisture content of 1.1% by mass, the dry powder material is heated to 650°C at a heating rate of 2°C / min in a nitrogen gas environment, and kept warm for 18 hours. The sintered product is crushed by a jet mill with a feeding frequency of 45Hz and a grading frequency of 32Hz to obtain a lithium iron manganese phosphate positive electrode material. The Dv50 of the obtained lithium iron manganese phosphate is 0.63μm, the manganese-iron ratio is 6:4, and the carbon content in the lithium iron manganese phosphate is 1.8%.

[0085] (2) Preparation of positive electrode sheet

[0086] The positive electrode active material (NCM+LMFP, the mass ratio of NCM and LMFP is 60:40), the conductive agent (SP+CNT), and the binder are pre-mixed at a low speed according to the mass ratio of 95:2.5:2.5, and the order of adding materials is half of the main material + auxiliary material + half of the main material; then N-methylpyrrolidone is added to make a mixed solution with a solid content of 64%; then, an appropriate amount of dispersant is added, and the mixture is dispersed at high speed for 4 hours, and N-methylpyrrolidone is continuously added to adjust the viscosity to obtain a uniform positive electrode slurry with a viscosity of 4000-8000mPa·s and a solid content of about 61%. Afterwards, carbon-coated aluminum foil is selected as the positive electrode current collector, and the positive electrode slurry is coated on the surface of the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling, stripping, and cutting.

[0087] (3) Preparation of negative electrode sheet

[0088] The negative electrode material graphite, the conductive agent carbon black, the thickener CMC, and the binder SBR are mixed in a mass ratio of 94.3:1.5:1.2:3, and the solvent deionized water is added. The mixture is stirred in a stirrer until the system becomes uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode collector copper foil, placed in an oven for drying, and rolled and cut to obtain a negative electrode sheet.

[0089] (4) Preparation of electrolyte

[0090] Organic solvents ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1:1. In an argon atmosphere glove box with a water content of <10 ppm, fully dried lithium hexafluorophosphate was dissolved in the above organic solvents to a content of 1 mol / L, and mixed evenly to obtain an electrolyte.

[0091] (5) Preparation of secondary batteries

[0092] The positive electrode sheet, the separator (polyethylene), and the negative electrode sheet are wound in order to obtain a bare cell; the bare cell is placed in an outer package, vacuum dried, injected with electrolyte, left to stand, formed, shaped, and capacity divided to obtain a secondary battery.

[0093] Example 2

[0094] Embodiment 2 provides a secondary battery, which is different from Embodiment 1 in that the mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron oxide in the positive electrode material of Embodiment 2 is 70:30.

[0095] Example 3

[0096] Embodiment 3 provides a secondary battery, which is different from Embodiment 1 in that the mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron oxide in the positive electrode material of Embodiment 3 is 50:50.

[0097] Example 4

[0098] Embodiment 4 provides a secondary battery, which differs from Embodiment 1 in that the mass ratio of lithium nickel cobalt manganese oxide and lithium manganese iron oxide in the positive electrode material of Embodiment 4 is 80:20; the preparation method of lithium nickel cobalt manganese oxide is different, and the specific preparation method is as follows: the coating source in step S03 is TiO2.

[0099] Example 5

[0100] Example 5 provides a secondary battery, which is different from Example 1 in that the mass ratio of lithium nickel cobalt manganese oxide and lithium manganese iron oxide in the positive electrode material of Example 5 is 20:80; the preparation method of lithium nickel cobalt manganese oxide is different, and the specific preparation method is as follows: the coating source in step S03 is TiO2.

[0101] Example 6

[0102] Embodiment 6 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of the manganese iron lithium oxide in the positive electrode material of Embodiment 6 is different, and the specific preparation method is as follows:

[0103] In the step S01 of preparing lithium iron manganese oxide, the doping sources are magnesium sulfate and titanium oxide.

[0104] Example 7

[0105] Embodiment 7 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of the lithium nickel cobalt manganese oxide in the positive electrode material of Embodiment 7 is different, and the specific preparation method is as follows:

[0106] In the step S01 of preparing lithium nickel cobalt manganese oxide, the molar ratio of nickel, cobalt and manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=70:10:20.

[0107] Example 8

[0108] Embodiment 8 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of lithium nickel cobalt manganese oxide in the positive electrode material of Embodiment 8 is different, and the specific preparation method is as follows:

[0109] In the step S01 of preparing lithium nickel cobalt manganese oxide, the molar ratio of nickel, cobalt and manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=80:10:10.

[0110] Example 9

[0111] Embodiment 9 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of lithium nickel cobalt manganese oxide in the positive electrode material of Embodiment 9 is different, and the specific preparation method is as follows:

[0112] In the step S01 of preparing lithium nickel cobalt manganese oxide, the molar ratio of nickel, cobalt and manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=90:5:5.

[0113] Example 10

[0114] Embodiment 10 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of the lithium nickel cobalt manganese oxide in the positive electrode material of Embodiment 10 is different, and the specific preparation method is as follows:

[0115] In the preparation step S01 of lithium nickel cobalt manganese oxide, the molar ratio of nickel, cobalt and manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=90:5:5; the precursor reaction time is adjusted to 48h, and the prepared sample is polycrystalline.

[0116] Embodiment 11

[0117] Embodiment 11 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of the lithium nickel cobalt manganese oxide in the positive electrode material of Embodiment 11 is different, and the specific preparation method is as follows:

[0118] In the preparation step S01 of lithium nickel cobalt manganese oxide, the molar ratio of nickel, cobalt and manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=90:5:5; and in the preparation of the positive electrode plate, the positive electrode active material NCM:LMFP=80:20.

[0119] Example 12

[0120] Embodiment 12 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of the lithium nickel cobalt manganese oxide in the positive electrode material of Embodiment 12 is different, and the specific preparation method is as follows:

[0121] In the preparation step S01 of lithium nickel cobalt manganese oxide, the molar ratio of nickel, cobalt and manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=90:5:5; and in the preparation of the positive electrode sheet, the positive electrode active material NCM:LMFP=20:80.

[0122] Embodiment 13

[0123] Embodiment 13 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of the manganese iron lithium oxide in the positive electrode material of Embodiment 13 is different, and the specific preparation method is as follows:

[0124] In the preparation step S01 of lithium manganese iron oxide, the molar ratio of Li, Mn, Fe, Mg and P is 1: 0.5: 0.48: 0.02: 1. In step S03, the amount of sucrose added is 1.5wt% of the precursor.

[0125] Embodiment 14

[0126] Embodiment 14 provides a secondary battery, which is different from Embodiment 1 in that the preparation method of the manganese iron lithium oxide in the positive electrode material of Embodiment 14 is different, and the specific preparation method is as follows:

[0127] In the preparation step S01 of lithium manganese iron oxide, the molar ratio of Li, Mn, Fe, Mg and P is 1: 0.8: 0.18: 0.02: 1. In step S03, the amount of sucrose added is 2 wt% of the precursor.

[0128] Comparative Example 1

[0129] Comparative Example 1 provides a secondary battery, which is different from Example 1 in that the preparation method of the lithium nickel cobalt manganese oxide in the positive electrode material of Comparative Example 1 is different, and the specific preparation method is as follows:

[0130] In the preparation step S01 of lithium nickel cobalt manganese oxide, the molar ratio of nickel, cobalt and manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=90:5:5; and in the preparation of the positive electrode sheet, the positive electrode active material NCM:LMFP=90:10.

[0131] Comparative Example 2

[0132] Comparative Example 1 provides a secondary battery, which is different from Example 1 in that the preparation method of the lithium nickel cobalt manganese oxide in the positive electrode material described in Comparative Example 2 is different, and the specific preparation method is as follows:

[0133] In the preparation step S01 of lithium nickel cobalt manganese oxide, the molar ratio of nickel cobalt manganese elements in the nickel cobalt manganese sulfate solution is Ni:Co:Mn=90:5:5; and in the preparation of the positive electrode plate, the positive electrode active material NCM:LMFP=10:90.

[0134] The physical properties of lithium nickel cobalt manganese oxide and lithium manganese iron oxide in Examples 1 to 14 and Comparative Examples 1 to 2 are shown in Tables 1 and 2, and the physical properties of the positive electrode sheet are shown in Table 3.

[0135] Table 1

[0136]

[0137]

[0138] Table 2

[0139] Manganese to Iron Ratio Dv50 / μm The Me Element Carbon content / % <![CDATA[Δc LMFP / %]]> <![CDATA[δ LMFP (011)]]> Example 1 6:4 0.63 Mg 1.8 1.58 0.18 Example 2 6:4 0.63 Mg 1.8 1.52 0.6 Example 3 6:4 0.63 Mg 1.8 1.76 0.22 Example 4 6:4 0.63 Mg 1.8 1.45 0.14 Example 5 6:4 0.63 Mg 1.8 1.87 0.24 Example 6 6:4 0.63 Ti+Mg 1.8 1.57 0.17 Example 7 6:4 0.63 Mg 1.8 1.56 0.15 Example 8 6:4 0.63 Mg 1.8 1.54 0.16 Example 9 6:4 0.63 Mg 1.8 1.45 0.17 Example 10 6:4 0.63 Mg 1.8 1.43 0.13 Embodiment 11 6:4 0.63 Mg 1.8 1.42 0.24 Example 12 6:4 0.63 Mg 1.8 1.94 0.28 Embodiment 13 5:5 0.50 Mg 1.5 1.51 0.15 Embodiment 14 8:2 1.00 Mg 2.0 1.97 1.23 Comparative Example 1 6:4 0.63 Mg 1.8 1.36 0.21 Comparative Example 2 6:4 0.63 Mg 1.8 2.27 0.36

[0140] Table 3

[0141]

[0142] The rate performance and cycle performance of the secondary batteries prepared in the embodiments and comparative examples were tested. The specific test results are shown in Table 4.

[0143] The test method for 45℃ cycle performance is:

[0144] At 45°C, the soft-pack battery is charged at a constant current of 1.0C to 4.35V, then charged at a constant voltage to a current less than or equal to 0.05C, and then discharged at a constant current of 1.0C to 2.5V. The discharge capacity at this time is recorded as the first discharge capacity. The soft-pack battery is subjected to a cyclic charge and discharge test according to the above process, and the discharge capacity is recorded each time. The capacity retention rate is the ratio of the discharge capacity of the nth cycle to the first discharge capacity.

[0145] The test method for rate performance is:

[0146] Discharge: At 25°C, the soft-pack battery was charged to 4.35V at a constant current and constant voltage of 1C, and then discharged to 2.5V at different constant current rates (0.33C / 1C / 2C / 3C / 4C). Taking the capacity at 0.33C as 100%, the ratios of the discharge capacity at other rates to the discharge capacity at 0.33C were calculated in turn to obtain the discharge capacity retention rate after the rate was increased.

[0147] Double charge: At 25°C, the soft-pack battery was discharged at a constant current of 1C to 2.5V, and then charged at different constant current rates (0.33C / 1C / 2C / 3C / 4C) to 4.35V. Taking the capacity at 0.33C as 100%, the ratios of the charging capacity at other rates to the charging capacity at 0.33C were calculated in turn to obtain the charging capacity retention rate after the rate was increased.

[0148] The DSC test method is:

[0149] At 25°C, the soft-pack battery was charged to 4.35V at a constant current and constant voltage of 1C, and then the battery cell was disassembled in a drying room, the entire positive electrode piece was taken out and placed in a beaker, and an appropriate amount of high-purity anhydrous dimethyl carbonate (DMC) was poured into it for cleaning for 10 minutes, and then it was left to dry until there was no obvious electrolyte residue on the surface of the positive electrode piece; 4.95mg~5.05mg of the positive electrode piece was weighed and placed in the high-pressure crucible of the differential scanning calorimeter and sealed, and the sample was heated at a heating rate of 5°C / min, and the data of the change of the sample heat flow with temperature were recorded to obtain the DSC spectrum, and the integral area of ​​the exothermic peak, that is, the heat release (J / g) was obtained.

[0150] Table 4

[0151]

[0152]

[0153] From the above embodiments and comparative examples, it can be seen that by selecting appropriate NCM and LFMP and uniformly blending them in appropriate proportions, the final product can take into account the advantages of both, and achieve a balance between battery performance and material cost.

[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises lithium nickel cobalt manganese oxide and lithium manganese iron oxide; When the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum expansion change rate Δc of the lattice of the lithium nickel cobalt manganese oxide in the c-axis direction is NCM ≤2.5%, the maximum expansion change rate Δc of the lattice of the manganese iron lithium oxide in the c-axis direction LMFP ≤2.0%.

2. The positive electrode material according to claim 1, characterized in that The molecular formula of the lithium nickel cobalt manganese oxide is Li x Ni y Co z Mn k M p O2, wherein 0.9≤x≤1.1, 0.5<y<1, 0<z<0.2, 0<k<0.5, 0≤p≤0.1, and M comprises at least one of B, Y, Nb, In, La, Zr, Ce, W, Al, Ti, Sr, Mg, Sb, V, Zn, Cu, Cr, and Fe.

3. The positive electrode material according to claim 1, characterized in that At least part of the surface of the lithium nickel cobalt manganese oxide also has a coating layer, and the coating layer contains oxides of one or more elements selected from the group consisting of Li, Na, B, Ca, Zn, Zr, Al, Sr, Mg, W, Y, Nb, Ti, Ru, and Mo.

4. The positive electrode material according to claim 1, characterized in that The manganese iron lithium oxide contains the Me element, and the Me element contains at least one of Al, Ti, V, Mg, Mo, Zr, W, Sr, Cr, La, and Ce.

5. The positive electrode material according to claim 1, characterized in that The manganese iron lithium oxide includes primary particles with an average particle size of 50 to 200 nm.

6. The positive electrode material according to claim 1, characterized in that The mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron oxide in the positive electrode material is 2:8 to 8:

2.

7. The positive electrode material according to claim 1, characterized in that When the positive electrode material is charged from a 10% de-lithiation state to an 80% de-lithiation state at a rate of 0.1C, the maximum deviation angle δ of the (003) crystal plane XRD diffraction peak of the lithium nickel cobalt manganese oxide NCM (003)≤0.6°, the maximum deviation angle δ of the (011) crystal plane XRD diffraction peak of the manganese iron lithium oxide LMFP (011)≤0.3°.

8. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 7.

9. The secondary battery according to claim 8, characterized in that: The mass concentration deviations of nickel and iron in the positive electrode sheet are both less than 20%.

10. The secondary battery according to claim 8, characterized in that: The film resistance of the positive electrode plate is less than 1Ω.

11. The secondary battery according to claim 8, characterized in that: The specific surface area of ​​the positive electrode sheet is 2 to 10 m 2 / g.

12. The secondary battery according to claim 8, characterized in that: The positive electrode plate has a porosity of 10% to 40%.

13. An electrical equipment, characterized in that: The electrical device comprises the secondary battery according to any one of claims 8 to 12.